Penggunaan Gelar Tanpa Hak Ditinjau dari Peraturan Perundang-Undangan - Rifki Asrofi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Social media has recently been abuzz with the polemic of high school students graduating using MIPA degree sashes. The use of academic degrees without rights can cause misunderstandings and damage the integrity of academic symbols, which should be maintained authentically in order to respect the true value of education. This type of research is normative juridical, examining laws, data from literature studies, analyzed descriptively qualitatively. The provisions for the use of degrees have been regulated in several laws and regulations in Indonesia. The use of academic degrees without rights violates the Higher Education Law, Permendikbudristek No. 6 of 2022 and the Criminal Law with the threat of a 10-year prison sentence or a category VI fine. It would be better if someone does not carelessly create or name a degree or use a degree without rights, because it is detrimental to academic integrity and violates the law, creating a false impression.